Biodiversity assessment of spiders in Pulau Ubin and Sungei Buloh Wetland Reserve. - Heng, Kelvin Teck Yang. (2012)
Over a four-month period, surveys were carried out to assess the biodiversity of spiders on Pulau Ubin and Sungei Buloh Wetland Reserve. From these sites, survey plots were selected